PHONEME IN ENGLISH AND TONTEMBOAN LANGUAGE (CONTRASTIVE ANALYSIS) - Jennifer Mamoto; Donald R. Lotulung; Maya Pinkan Warouw (Paratext: International Journal of Language and Literature, 2025)
This research, Phoneme in English and Tontemboan Language, is aimed to identify and classify the phoneme forms, distribution patterns, and phonotatic systems of English and Tontemboan languages, then contrasts the results of the two languages. This research used qualitative methods, and to analyze the data the writer uses Fromkin's theory (2017), Finegan's theory (2015), and Thomasz's theory (1990). The result of this research are as follow: in the English data, 23 consonant phonemes were found, namely /b/, /ʧ/, /d/, /ð/, /f/, /g/, /h/, /k/, /l/, /m/, /n/, /ŋ/, /p/, /r/, /ɹ/, /s/, /ʃ/, /t/, /θ/, /v/, /w/, /z/, and 12 vowel phonemes: /a/, /ɑ/, /ʌ/, /ɪ/, /i/, /u/, /ʊ/, /e/, /ə/, /ɜ/, /ɔ/. The Tontemboan language data has 18 consonant phonemes, namely /b/, /p/, /t/, /d/, /k/, /g/, /?/, /c/, /s/, /h/, /l/, /r/, /m/, /n/, /ŋ/, /w/, /j/, /y/, and 6 vowel phonemes: /a/, /i/, /E/, /ə/, /o/, /u/. The difference between English and Tontemboan phoneme forms is that Tontemboan language does not have several phonemes in English, namely /z/, /θ/, /ð/, /ʃ/, /ɹ/, and /ʧ, on the other hand English does not have the phoneme /ʔ/ where this phoneme is exist in Tontemboan language. These two languages have some phonemes in common, namely /b/, /p/, /t/, /d/, /k/, /g/, /c/, /s/, /h/, /l/, /r/, /m/, /n/, /ŋ/, /w/, /j/, /y/. /a/, /i/, /ə/, /o/, and /u.